No clinical benefit of empirical antimicrobial therapy for pediatric diarrhea in a high usage, high resistance setting. - Duong, V; Tuyen, H; Minh, P; Campbell, J; Phuc, H; Nhu, T; Tu, L; Chau, T; Nhi, L; Hung, N; Ngoc, N; Huong, N; et al. (Oxford University Press, 2017)
Background Pediatric diarrheal disease presents a major public health burden in low-middle income countries. The clinical benefits of empirical antimicrobial treatment for diarrhea are unclear in settings that lack reliable diagnostics and have high antimicrobial resistance (AMR). Methods We conducted a prospective multi-center cross-sectional study of pediatric patients hospitalized with diarrhea containing blood and/or mucus in Ho Chi Minh City, Vietnam. Clinical parameters, including disease outcome and treatment, were measured. Shigella, non-typhoidal Salmonella (NTS), and Campylobacter were isolated from fecal samples and their antimicrobial susceptibility profiles were determined. Statistical analyses, comprising Log-rank tests and accelerated failure time models, were performed to assess the effect of antimicrobials on disease outcome. Results Among 3,166 recruited participants (median age 10 months, IQR 6.5-16.7 months), one-third (1,096/3,166) had bloody diarrhea and 25% (793/3,166) were culture-positive for Shigella, NTS, or Campylobacter. Over 85% (2,697/3,166) of patients were treated with antimicrobials; fluoroquinolones were the most commonly administered antimicrobials. AMR was highly prevalent among the isolated bacteria, including resistance against fluoroquinolones and third generation cephalosporins. Antimicrobial treatment and multidrug resistance status of the infecting pathogens were found to have no significant effect on outcome. Antimicrobial treatment was significantly associated with an increase in the duration of hospitalization in particular groups of diarrheal diseases. Conclusions In a setting with high antimicrobial usage and high AMR our results imply a lack of clinical benefit for treating diarrhea with antimicrobials; adequately powered randomized controlled trials are required to assess the role of antimicrobials for diarrhea.